2004
DOI: 10.1055/s-2004-832619
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profiling ofHypericum(St. John’s Wort) Species by Nuclear RibosomalITSSequence Analysis

Abstract: A PCR-based DNA amplification method was applied to genetically distinguish the popular dietary supplement Hypericum perforatum L. (common St. John's Wort) from other related Hypericum species. Nuclear ribosomal gene sequences of the internal transcribed spacer (ITS) region were analyzed for 50 Hypericum taxa native to the Old and New Worlds, representing 11 of the 36 currently accepted taxonomic sections. This study provides a genetic method for authentication of commercial H. perforatum preparations. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 9 publications
4
43
1
Order By: Relevance
“…Ascyrum. On the contrary, ITS sequence data proved the monophyly of Myriandra (Crockett et al 2004). The inconsistencies between gene trees based on nuclear and plastid markers are not uncommon and could be attributed to lineage sorting, hybridization / reticulation, nonhomologous sampling of duplicated gene, or chloroplast capture (Hendy & Penny 1989;Doyle 1997;Maddison 1997;Sang & Zhong 2000;Tsitrone et al 2003; …”
Section: Pcr Amplifications and Restriction Of Pcr Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascyrum. On the contrary, ITS sequence data proved the monophyly of Myriandra (Crockett et al 2004). The inconsistencies between gene trees based on nuclear and plastid markers are not uncommon and could be attributed to lineage sorting, hybridization / reticulation, nonhomologous sampling of duplicated gene, or chloroplast capture (Hendy & Penny 1989;Doyle 1997;Maddison 1997;Sang & Zhong 2000;Tsitrone et al 2003; …”
Section: Pcr Amplifications and Restriction Of Pcr Productsmentioning
confidence: 99%
“…Despite the economical potential of the Hypericum species, there are only two references on the application of molecular markers in Hypericum: phylogenetic studies both employing nuclear rDNA ITS sequence data (Crockett et al 2004;Park & Kim 2004). Preliminary PCR-RFLP analysis of cpDNA showed a considerable degree of interspecific polymorphism and confirmed the applicability of this method in phylogenetic investigations in the genus Hypericum (Hazler Pilepić 2002).…”
Section: Introductionmentioning
confidence: 98%
“…According to Howard et al ., the nuclear ribosomal Internal transcribed spacer (ITS1 and ITS2) DNA region is the most suitable ‘‘barcode’’ for primer creation (through PCR), plant species distinguishing and detection of adulterants. Many DNA barcoding studies on Hypericum species identification have been conducted including those of Crockett et al ., Park and Kim, Howard et al ., Pilepic et al . and Costa et al …”
Section: Dna Barcodingmentioning
confidence: 99%
“…The authors proposed this technique for the authentication of SJW in commercial products (species level), but they concluded that the technique was not sufficient on subspecies level. The technique was also useful for evaluation of phylogenetic affinities within the genus …”
Section: Dna Barcodingmentioning
confidence: 99%
“…This could be attributed to the fact that the cultivated varieties used in this study were developed in Germany and Denmark. Crockett et al (2004) study provides a genetic method for authentication of commercial H. perforatum preparations and allows a preliminary assessment of phylogenetic relationships within the genus, revealing three strongly supported monophyletic clades, plus several secondary monophyletic groupings. Using internal transcribed spacer (ITS) gene sequences, they were able to distinguish H. perforatum from all other species of Hypericum included in this study.…”
Section: Introductionmentioning
confidence: 99%